Perencanaan Sistem Penyaluran dan Pengolahan Air Limbah Domestik Industri Produksi Bahan Kimia PT X Jawa Timur - Muhammad Abdus Salam Jawwad; Nuraini Safitri (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
PT X is a chemical manufacturing company specializing in the production of phosphoric acid and sulfuric acid. In addition to waste generated from production processes, PT X also produces domestic wastewater originating from supporting activities such as employee barracks, offices, and laundry facilities. This domestic wastewater contains parameters that can potentially pollute the environment, such as BOD, COD, TSS, ammonia, and Total Coliform, some of which exceed the quality standards set by the Minister of Environment Regulation No. 68 of 2016. This study aims to design an effective Domestic Wastewater Treatment Plant (DWTP) system to process the domestic wastewater of PT X. The proposed DWTP system consists of a collection tank, Anaerobic Baffled Reactor (ABR), Aerobic Biofilter, and disinfection unit. Each unit is designed to reduce pollutant parameters to meet quality standards. Based on the calculations, this system can handle a wastewater flow rate of 21.91 m³/day with high treatment efficiency for critical parameters. The study results indicate that the proposed DWTP design can reduce environmental pollution, improve wastewater treatment operational efficiency, and comply with applicable regulations. Implementing this system is highly recommended to ensure environmental sustainability and the continued operations of PT X.